Can Nuclear Energy Contribute to the Transition Toward a Low-carbon Economy? The Japanese Case - Ishida, Hazuki (International Journal of Energy Economics and Policy, 2018)
This paper examines the impact of nuclear energy consumption on CO2 emissions in Japan over the period 1970–2010. Using an autoregressive distributed lag (ARDL) bounds testing approach, we develop bivariate and multivariate models specifying CO2 emissions as the dependent variable. The results reveal that in the long run, there is no evidence that an increase in nuclear energy consumption leads to a decrease in CO2 emissions other than price-induced effects from the decrease in electricity demand given the increase in electricity prices. These results suggest that whether nuclear energy is a low-carbon electricity generation option remains an open question from a long-term perspective. Keywords: nuclear energy, CO2 emissions, cointegration, autoregressive distributed lag JEL Classifications: Q43, Q50